2014
DOI: 10.1007/s10198-014-0583-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of integrated care in frail elderly using the ICECAP-O and EQ-5D: does choice of instrument matter?

Abstract: Economic evaluations likely undervalue the benefits of interventions in populations receiving both health and social services, such as frail elderly, by measuring only health-related quality of life. For this reason, alternative preference-based instruments have been developed for economic evaluations in the elderly, such as the ICECAP-O. The aim of this paper is twofold: (1) to evaluate the cost-effectiveness using a short run time frame for an integrated care model for frail elderly, and (2) to investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 60 publications
1
60
0
Order By: Relevance
“…The results of cost-effectiveness analysis are indeed influenced by the reliability and content of outcome measures, as was shown in a recent economic evaluation in which personal health budgets were considered cost-effective using ASCOT and not cost-effective using the EQ-5D [57]. Two other studies showed that conclusions of the economic evaluation of integrated care in frail elderly [58] and telehealth for patients with long-term conditions [59] did not differ using ICECAP-O or the EQ-5D, although at the same level of willingness to pay, interventions had a higher probability of cost-effectiveness using ICECAP-O.…”
Section: Discussionmentioning
confidence: 89%
“…The results of cost-effectiveness analysis are indeed influenced by the reliability and content of outcome measures, as was shown in a recent economic evaluation in which personal health budgets were considered cost-effective using ASCOT and not cost-effective using the EQ-5D [57]. Two other studies showed that conclusions of the economic evaluation of integrated care in frail elderly [58] and telehealth for patients with long-term conditions [59] did not differ using ICECAP-O or the EQ-5D, although at the same level of willingness to pay, interventions had a higher probability of cost-effectiveness using ICECAP-O.…”
Section: Discussionmentioning
confidence: 89%
“…While the ASCOT instrument can be used in a QALY estimation (so-called social care QALYs) as it is anchored at dead, the ICECAP measures should not be. Makai et al [39] estimated both capability QALYs and health QALYs (using the EQ-5D) and compared them; this is incorrect. A CUA using an ICECAP instrument should estimate the incremental cost per unit of capability gained.…”
Section: Outstanding Issuesmentioning
confidence: 97%
“…This then raises the question: what is the value of a capability improvement? Aside from Makai et al [39] and Henderson et al [54], no other economic evaluation employing an ICECAP measure has to date produced an ICER with respect to the measure. This is likely to be due to the measure being new and unfamiliar to decision makers, so the evaluation team has used EQ-5D/ QALYs (as Henderson et al [54] do) or a clinical measure [55].…”
Section: Outstanding Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Capability wellbeing has so far been utilised alongside health-related measures of quality of life using the maximisation principle and not in terms of equalisation or sufficient capability as recommended [91]. Even as such, a parallel use of the ICECAP measures in economic evaluations alongside the commonly used instruments may act as a safety-pillar to basecase analyses if results are verified [92,93]. The two instruments, however, are quite distinct in what they measure and, therefore, the health effects of an intervention may not always be translated into a capability improvement, and similarly an absence of a health effect may not always imply the absence of important capability wellbeing gains.…”
Section: (Table 5 About Here)mentioning
confidence: 99%